Simultaneous coronary artery and bilateral carotid artery stenting in the same setting: first ever experience in Bangladesh - Dutta, Bijoy; Kumar Karmoker, Kajal; Rashid, Md Bazlur; Siddika, Ayesha; Kashyapi, Basudev; Rahman, Mohammad Walidur; Javed, Adib Al; Saha, Santosh Kumar (International Journal of Research in Medical Sciences, 2025)
The coexistence of coronary artery disease (CAD) and carotid artery stenosis (CS) is relatively common, particularly among elderly patients. However, the optimal management of patients with simultaneous severe CAD and bilateral CS remains a subject of clinical debate, as multiple treatment strategies exist. We present the case of a 66-year-old male who was admitted to the National Institute of Cardiovascular Diseases (NICVD), Bangladesh, with recurrent syncopal episodes and exertional chest pain. Diagnostic evaluation with Digital Subtraction Angiography (DSA) and Coronary Angiography (CAG) revealed bilateral severe internal carotid artery stenosis along with significant stenosis of the right coronary artery (RCA). The patient was successfully treated with a one-stage percutaneous intervention involving right coronary artery stenting followed by bilateral internal carotid artery stenting. To the best of our knowledge, this is the first documented case of such a simultaneous triple-vessel intervention in Bangladesh.